Legal Analysis of Compensation for Infringement of Trademarks of Non-Synonymous Goods in Indonesia - Fransisca Giovany Andri (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This paper abstracts on damages for infringement of marks of non-similar goods, the protection for trademarks has been regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications, yet in reality, infringements against trademarks still occur. This research discusses the application of the first-to-file principle and compensation in cases of dissimilar goods trademark infringement. The research employs a normative juridical research method with a legislative approach. The legal sources utilized are secondary data obtained from literature materials, with primary legal materials including Decision Number 836 K/Pdt.Sus-HKI/2022 and Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The data analysis method used in this research is qualitative normative analysis. The research findings indicate that the first-to-file principle is applied not only to trademark registration for similar goods but also to dissimilar goods. The compensation that can be awarded to the legitimate trademark owner is immaterial compensation, the amount of which is determined by the judge considering the positions of the parties involved. The Directorate General of Intellectual Property in examining trademark registration applications must be more meticulous, and judges, in determining the amount of immaterial compensation, must prioritize justice.